ATTITUDES OF AGRICULTURAL STUDENTS TOWARD CAREERS IN THEAGRICULTURE SECTOR - ARPITA SHARMA KANDPAL (The Journal of Research, PJTSAU, 2026)
The agriculture sector, as a linchpin of global food security and sustainable development, relies heavily on a skilled workforce. Recognizing the pivotal role of undergraduate agriculture students in shaping the future of agriculture, this research seeks to unravel the intricacies of their attitudes towards choosing a career in the agriculture sector. (Onu and Ikehi, 2013).